Mechanical properties measurement using ultrasonic lamb wave - Koh, John Taiwei. (2011)
This project aims to use Lamb waves to predict the properties of materials. Due to the complexity of Lamb waves and their governing equations, computational methods are required to numerically solve these equations. This project uses the bisection method in MATLAB to solve the equations. Firstly, the Rayleigh-Lamb equations for the symmetric and antisymmetric Lamb waves, which are a function of the material properties, are solved for their phase and group velocity. An example dispersion curve for CFRP and aluminium alloy 2024-T3 based on the algorithm has been given as well and compared with commercial software to verify its accuracy. Next, based on measured symmetric and antisymmetric Lamb wave velocities, it becomes possible to determine the in-plane mechanical properties of the material. Two methods have been introduced, using tables and using the axial and Rayleigh waves. The values are in concordance with the initial data used to generate the Lamb wave velocities. Furthermore, this project also aims to attempt to use the transfer matrix method to derive the wave velocities. However, the results from the algorithm need verification for accuracy and consistency. Some preliminary work has been done to explore the possibility of using the transfer matrix method to determine the material properties.